Effect of Photo Irradiation on the Anaerobic Digestion of Waste Sewage Sludge-Reduced Methane and Hydrogen Sulfide Productions - Shotaro Toya; Shunsuke Iriguchi; Kohei Yamaguchi; Toshinari Maeda (Fermentation, 2023)
Since a large amount of sewage sludge (WSS) is generated daily, exploring effective methods for utilizing WSS is necessary. Although a photo-fermentation system sometimes alters the characteristics of microbial functions, there have been no attempts to perform photo-fermentation using WSS, which is regularly treated via dark fermentation. In this study, the effect of photo-fermentation (photo-irradiation) on anaerobic digestion using WSS was revealed. Photo-irradiation during the anaerobic digestion of WSS significantly reduced the amount of methane and hydrogen sulfide. Methane production was also reduced 5.6-fold at 13 days under light conditions, whereas hydrogen sulfide was consumed almost completely at 6 days. However, it was shown that the activity of sulfate-reducing bacteria in WSS under light treatment increased. Photo-irradiation also stimulated the growth of green sulfur bacteria and induced anoxygenic photosynthesis, via which process the fermented samples turned green in a manner that was correlated with their consumption of hydrogen sulfide. The production of organic acids was lowered in the samples that were irradiated using light. Finally, dark/light switching fermentation was only able to reduce hydrogen sulfide while methane production remained the same. The amounts of methane and hydrogen sulfide were 35 mmol/g VS, and they were undetected at 58 days in photo-irradiated samples compared to the control samples that produced 37 mmol/g VS of methane and 15 ppm/g VS of hydrogen sulfide.